Graduates of Applied Bachelor Study Program (D4) Marketing Management Positioning in Perspective of Industry Interest Trends as a Global Job Market - Isnaini - Nurkhayati; Azizah - Azizah; Endang - Sulistyani; Winarto - Winarto; Febrina - I (Politeknik Negeri Semarang, 2022)
The Directorate General of Vocational Education of the Ministry of Education and Culture continues to make various kinds of breakthroughs to produce competent human resources according to the demands of the business world and the industrial world. One of the programs carried out is the upgrading D3 program become an applied bachelor or D4. Based on this, the Marketing Management Study Program, Business Administration Department, Politeknik Negeri Semarang, wishes to open an Applied Undergraduate Study Program (D4). However, at this time it is unknown how the positioning and trend of industrial interest towards graduates of the Applied Bachelor Study Program (D4) in Marketing Management. Therefore, it is necessary to find out whether the Applied Undergraduate Study Program (D4) Marketing Management Department of Business Administration Politeknik Negeri Semarang deserves to be opened from an industrial perspective so that later they will get awards and better careers because D4 graduates are already equivalent to S1. In this research, a survey was conducted with quantitative and qualitative analysis. The data sources of this research are companies that become the place for on the job training for third grade students, partner companies for the P3TV program of the Marketing Management Study Program and several other related companies that have the potential to absorb graduates of the Applied Bachelor Study Program (D4) in Management. Marketing. Based on the results of the research above, it can be seen that partially both positioning and interest have a significant effect on feasibility and simultaneously both positioning and interest have an effect on feasibility. Therefore, it can be concluded that the Applied Bachelor Study Program (D4) in Marketing Management deserves to be opened in the perspective of global job market trends because it has a high interest and positioning index.